Diurnal activity and resting time allocation of the West African giraffe in an agropastoral human-dominated landscape - Hejcmanová, Pavla; Gašparová, Kateřina; Fedorova, Tamara; Vukelić, Mara; Fennessy, Julian; Moussa Zabeirou, Abdoul Razack; Rabeil, Thomas; Brandlová, Karolína (Frontiers in Conservation Science, 2024)
Resting is an integral component of animal behavior, contributing to one's fitness through careful optimization strategies. In large herbivores, resting periods are driven by availability of food, presence of predators, and thermoregulation. A combination of these drivers leads to high variability in resting behaviors and their time allocation throughout the day. However, these drivers are rarely evaluated in the wild. Megaherbivores, including giraffe (Giraffa spp.), adopt social resting strategies which enables them to optimize the cost-benefit ratio, with rest and vigilance varying with group size and composition. We investigated resting behavior of the West African giraffe (G. camelopardalis peralta) living in a human populated landscape dominated by agropastoralism activities in Niger. Through direct observation we evaluated the influence of group size and composition, and presence of livestock and humans on giraffe resting behavior. We concluded that giraffe increased their resting time with shorter distance to other giraffe and livestock. Livestock did not negatively impact giraffe behavior; rather, they provided a kind of "safe environment". Human presence resulted in only minor changes in vigilance of giraffe and did not significantly affect their resting time. Our findings highlight a positive instance of humangiraffe coexistence in a human dominated landscape, attributed to the long-term benefits of conservation efforts.